Pengaruh Pendidikan Ekonomi Digital terhadap Literasi Keuangan Generasi Muda - Hutasuhut, Saidun; Siagian, Irma; sinaga, Anisa fitria; Lubis, Atika Atayarisah; Amelia, Regita; Saputra, Firman; Manurung, Eka Valentina (Jurnal Ilmiah Wahana Pendidikan, 2025)
In the current digital era, developments in information technology have influenced various aspects of life, including the economy and education. The aim of this research is to see how digital economic education influences financial literacy in the younger generation. The type of research used is quantitative research. The results of the partial regression test (T test) are at a significance level of 0.05 with a T value of 6.293 with a significance of 0.000 < 0.05. Meanwhile, the Ttable value is 2.034. Therefore Ha is accepted because the value of tcount is 6.293 > ttable 2.034 so it can be concluded that there is a significant influence between economic education on the financial literacy of the younger generation. Based on the correlation test results, the correlation test results show that there is a strong and positive relationship between digital economic education and the financial literacy of the younger generation. The correlation coefficient value of 0.793 indicates that the two variables have a close relationship.